(untitled) (Heritage, 2021)
After the parliamentary elections in Montenegro in 2020, there was a change of government for the first time since the introduction of multipartyism, and many actors and media claim that popular meme pages on Facebook played a significant role in the campaign that preceded this election result. The paper starts from the assumption that different analytical frameworks and theories dealing with meme as a unit form of conveying a political message are not sufficient to fully explain the role of meme pages in the election campaign in Montenegro. The author believes that the content analysis of individual memes is only one, narrower aspect of observation, and that the role of meme pages in the election campaign in Montenegro can be better explained if we look at them as opinion leaders by adapting the two-stage communication theory to the characteristics of new media and by distinguishing the 4 streams of communication on the Internet proposed by Thorson and Wales (Thorson and Wells, 2012). For the purposes of the research, we use discourse analysis and content analysis of the Facebook pages "MIMistarstvo onostranih poslova" and "It was very unpleasent / Psalm 118" in the period from 1 to 30 August 2020, as well as direct structured interviews with the administrators of the mentioned Facebook pages.